One-Step Green Synthesis of Metallic Nanoparticles Using Sodium Alginate - Valdez, Jesús; Gómez, Idalia (2016)
Metallic nanoparticles have been focus of research because of their characteristic properties, specifically the LSPR which can have wide applications in biomedical sciences and engineering. Currently, traditional physical and chemical methods can synthesize these nanoparticles but their disadvantages such as costs, time, effectiveness, and toxicity of precursors provide a wide range of problems for the synthesis of these nanoparticles. Recently, some natural polymers and organic compounds have been used for the synthesis of nanoparticles by green methods. In this study, we synthesize copper, silver, and gold nanoparticles using sodium alginate as reducing and stabilizing agent under microwave irradiation. The LSPR for each system was observed by UV-vis spectroscopy. Particle size distribution and zeta potential demonstrate the size and stability for these nanoparticles. FESEM and TEM microscopies have shown the size and morphology of these systems correlated with UV-vis, particle size distribution, and zeta potential analyses. The study demonstrates a rapid, facile, cheaper, and one-step green method of synthesis for these metallic nanoparticles being an alternative to the conventional methods used for synthesis of metallic nanoparticles.